2021
DOI: 10.1136/archdischild-2020-320962
|View full text |Cite
|
Sign up to set email alerts
|

Caring for critically ill adults in paediatric intensive care units in England during the COVID-19 pandemic: planning, implementation and lessons for the future

Abstract: ObjectiveTo describe the experience of paediatric intensive care units (PICUs) in England that repurposed their units, equipment and staff to care for critically ill adults during the first wave of the COVID-19 pandemic.DesignDescriptive study.SettingSeven PICUs in England.Main outcome measures(1) Modelling using historical Paediatric Intensive Care Audit Network data; (2) space, staff, equipment, clinical care, communication and governance considerations during repurposing of PICUs; (3) characteristics, inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 19 publications
1
32
0
Order By: Relevance
“…There are several forms of integration of the PICU to the hospital response, especially in a general hospital [ [19] , [20] , [21] , [22] , [23] , [24] ]. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There are several forms of integration of the PICU to the hospital response, especially in a general hospital [ [19] , [20] , [21] , [22] , [23] , [24] ]. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, COVID-19 in adults resulted in excess of 25,000 critical care admissions in ICUs in England, Wales and Northern Ireland in 2020 [ 29 ]. Some of the PICU capacity freed up by the reduced number of childhood admissions were then utilised to provide critical care for the adults [ 5 , 30 ]. Moreover, paediatric critical care staff were also redeployed in adult ICUs.…”
Section: Discussionmentioning
confidence: 99%
“…Several PICUs were either entirely or partially repurposed to provide adult critical care [ 5 ]. During the crisis most institutions reduced their planned surgical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Amid this, Sinha et al in this issue found creative ways for children's doctors to care for sick adults with COVID-19 disease. 3 In a carefully crafted rubric, the authors show how thoughtful planning and methodical implementation in England can mobilise emergency resources in a time of crisis. As such, their success met the demand to increase AICU resources during the early surge of the COVID-19 pandemic while still meeting the paediatric critical care needs of the country.…”
Section: Editorialmentioning
confidence: 99%